ACCEPTANCE AND COMMITMENT THERAPY FOR PARENTS OF CHILDREN WITH INTELLECTUAL DISABILITY - Fadriyana, Aulia Putri (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction – Intellectual disability is one of the most common disabilities of children worldwide, and it becomes a stress burden among parents. Acceptance and Commitment Therapy (ACT), which goals to increase valued action and behaviour in the present moment, has been suggested as an alternative approach. This literature review aimed to explore the effect of acceptance and commitment therapy for parents of children with intellectual disability. Methods – The searches of this literature review were conducted in Google Scholar, ScienceDirect, PubMed, and Wiley Library, ranging from 2010 to 2023. The literature search involved articles that focused on the effect of ACT in parents of children with intellectual disability. Results – Four research articles were included. All of the article’s studies are about the use of ACT in parents of children with intellectual disability, but in different interventions and study designs. Discuss – Most parents stated that the struggles of caring for a child with significant behavioural challenges, both emotionally and physically, and the level of isolation they experienced, consequently, was great enough to generate stress. This programme gives a new perspective on their difficulties, enhancing their ability to deal with stress, and enabling parents to maintain their emotional well-being by “getting back on the track” of what parents should be based on their personal values. Conclusion – ACT may play a significant role in helping to improve the psychological well-being of parents with intellectual disability child. However, further investigation with interventions for each group based on precipitating factors is required to evaluate and to predict when the right time is to do this therapy.